Antigen mobility regulates the dynamics and precision of antigen capture in the B cell immune synapse - Hannah C. W. McArthur; Anna T. Bajur; Maro Iliopoulou; Katelyn M. Spillane (Proceedings of the National Academy of Sciences, 2025)
B cells discriminate antigens in immune synapses by capturing them from antigen-presenting cells (APCs). This discrimination relies on the application of mechanical force to B cell receptor (BCR)-antigen bonds, allowing B cells to selectively disrupt low-affinity interactions while internalizing high-affinity antigens. Using DNA-based tension sensors combined with high-resolution imaging, we demonstrate that the magnitude, location, and timing of forces within the immune synapse are influenced by the fluidity of the antigen-presenting membrane. Transitioning antigens from a high-mobility to a low-mobility substrate significantly increases the probability and speed of antigen extraction while also improving affinity discrimination. This shift in antigen mobility also reshapes the synapse architecture, altering spatial patterns of antigen uptake. Despite these adaptations, B cells maintain consistent levels of proximal and downstream signaling pathway activation regardless of antigen mobility. They also efficiently transport internalized antigens to major histocompatibility complex class II (MHCII)-positive compartments for processing. These results demonstrate that B cells mount effective responses to antigens across diverse physical environments, though the characteristics of that environment may influence the speed and accuracy of B cell adaptation during an immune response.